(untitled) (Rupantaran: A Multidisciplinary Journal, 2021)
The Dhankuta district, situated in the Eastern part of the country, is a hot spot for floral diversity. The vegetation zone ranges from sub tropical Sal forest to cool temperate alpine forest. The study of wild edible plant of this area was an attempt to highlight the types of wild edible plants found and their mode of use in local people. Present study records 132 species of wild edible plants belonging to 63 families and 103 genera. Fruits are the most common edible parts of the wild edible plants followed by leaves, young shoot, root or tuber, seeds, flower, whole plants, bark, nectar, nuts, inflorescence and buds.